INTRINSIC ELEMENTS IN DIGITAL SHORT STORIES ‘THE OVAL POTRAIT” BY EDGAR ALAN POE - Martina Girsang; Bernardus Batara Tuahta Praditya Ginting; Asima Rohana Parulian Tamba; Anna Catharina Samosir; Jessica Anastasia Kianlin (Universitas Islam Sumatera Utara, 2023)
Literary works are created from human feelings; the emotions are written through words and give aesthetic value to the audience. A short story is a short form of narrative literature that works similarly to a novel but is not longer than a novel and the plot of the story is simpler and it can be finished in one sitting. A short story is not simply built by ‘words’, there are components or elements that build the story until the end. Recognizing and identifying the structure of a short story is important; it is one of the ways to show appreciation for the literature and help people understand the implied meaning in it. In this article, the findings are conducted through intrinsic elements analysis of the selected short story entitled “The Oval Portrait” by Edgar Alan Poe. The story is analyzed in digital form and it is taken from a website on the internet. The descriptive qualitative method is used in the article to help interpret the elements found in the story. The results show that there are four significant intrinsic elements in the short story: plot, character, setting and narrative perspective.